Consumer Acceptance Towards Digital Marketing: A Quantitative Study Among Consumers in Kuala Lumpur - Le, Eugene Loo Zhi; Khalid, Mutia Anggeraini Binti; Ahmad, Rahilah Binti (Electronic Journal of Business and Management, 2023)
This research project aims to investigate the acceptance of digital marketing among consumers in Kuala Lumpur. By examining the digital marketing landscape and its impact on consumer behaviour, this study seeks to uncover the factors that influence consumers’ attitudes and behaviours towards digital marketing strategies. To achieve this, the research project formulates research questions and develops three hypotheses, which are subsequently tested. the study incorporates a comprehensive review of relevant literature to provide insights into the acceptance of digital marketing and to substantiate the research inquiries and challenges. Primary data were collected through a survey questionnaire distributed to 150 respondents who are consumers in Kuala Lumpur, Malaysia. This research is conducted by using a quantitative research method, and the primary data collected were analysed by using the Social Science Statistics Package (SPSS) software. The major findings of the study shed light on the intricate relationship between the effectiveness of electronic word of mouth, trust established through data security measures, and environmental friendliness, all of which contribute to consumer awareness and acceptance of digital marketing. This research project provides insights that can contribute to a deeper understanding of consumer behaviour in the context of digital marketing and offers implications for businesses aiming to enhance their digital marketing strategies and outcomes.